Structure and biological action of analogs and derivatives of biogenic polyamines - O. S. Egorov; N. Yu. Borisova; E. Ya. Borisova; M. L. Rezhabbaev; E. Yu. Afanas’eva; E. V. Arzamastsev (Тонкие химические технологии)
Objectives. Biogenic polyamines are widely present in nature. They are characteristic of both protozoan cells and multicellular organisms. These compounds have a wide range of biological functions and are necessary for normal growth and development of cells. Violation of polyamine homeostasis can cause significant abnormalities in cell functioning, provoking various pathological processes, including oncological and neuropsychiatric diseases. The impact on the “polyamine pathway” is an attractive basis for the creation of many pharmacological agents with a diverse spectrum of action. The purpose of this review is to summarize the results of the studies devoted to understanding the biological activity of compounds of the polyamine series, comparing their biological action with action on certain molecular targets. Due to the structural diversity of this group of substances, it is impossible to fully reflect the currently available data in one review. Therefore, in this work, the main attention is paid to the derivatives, acyclic saturated polyamines.Results. The following aspects are considered: biological functionality, biosynthesis and catabolism, cell transport, and localization of biogenic polyamines in the living systems. Structural analogs and derivatives of biogenic polyamines with antitumor, neuroprotective, antiarrhythmic, antiparasitic, antibacterial, and other biological activities are represented; the relationship between biological activity and the target of exposure is reflected. It was found that the nature of the substituent, the number of cationic centers, and the length of the polyamine chain have a great influence on the nature of the effect.Conclusions. At present, the use of polyamine structures is restrained by cytotoxicity and nonspecific toxic effects on the central nervous system. Further research in the field of biochemistry, cell transport, and a deeper understanding of receptor interaction mechanisms will help making polyamines as the basis for potential drug formulation.